(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of intertrochanteric fractures treated with Proximal Femoral Nail Antirotation (PFNA). Methods: This descriptive study was conducted in Unit I, Department of Orthopedic Surgery, Jinnah Hospital Lahore from 25th May 2019 to 4th November 2021. All patients with unstable intertrochanteric fractures fulfilling the inclusion criteria undergone Proximal Femoral Nailing(PFNA). Post operative functional outcome was assessed at 6th months using Harris hip score and were categorized as excellent, good, fair, and poor. Result: The total number of patients in this study were 85. The mean age was 49.41±12.24 year. There were 56(65.88%) female patients and 29(34.12%) male. Left sided fracture was found in 44 (51.76%) patients whereas the right-side fracture found in 41 (48.23%) patients. Boyd and Griffin type III fracture was documented in 46 (54.11%) patients whereas the type IV fracture noted in 39 (45.88%) patients. The mean Harris hip score was 84.84±8.80. Excellent outcome was noted in 27(31.76%) patients and good in 38(44.71%) patients. Conclusion: Unstable intertrochanteric fractures treated with Proximal Femoral Nail Antirotation(PFNA) produced excellent and good functional outcome in majority of our patients. We recommend PFNA as treatment of choice for unstable intertrochanteric fractures